Calidad de cuidado de enfermería y satisfacción de los pacientes del área de tuberculosis en la IPRESS I-4 Bellavista Nanay - Iquitos – 2024 - Huanci Alvarado, Margot Rocio (2025)
He objective was to determine the relationship between the quality of nursing care and patient satisfaction in the tuberculosis area at IPRESS I-4 Bellavista Nanay Iquitos - 2024. It is a quantitative, non-experimental, descriptive, cross sectional and correlational study; the population consisted of 58 patients with tuberculosis. The techniques used were: survey and home visit, the instruments: Likert Scale on the quality of care and nursing care satisfaction questionnaire. The results obtained were: in relation to the quality of nursing care, 51.7% of patients report that the quality of nursing care is inadequate and 48.3% of patients report that the quality of nursing care is adequate. Regarding satisfaction with the quality of nursing care, 56.9% of patients feel dissatisfied with the care they receive from the nursing staff and 43.1% of patients feel satisfied with the care they receive. When comparing the quality of nursing care and patient satisfaction, p=0.037 was obtained. It was concluded that there is a relationship between the quality of nursing care and patient satisfaction.